Urgensi Administrasi dalam Pengadaan Sistem Informasi Manajemen di SMP Telkom Purwokerto - Diasworo, Oeky; Aliyah, Himatun; Nurfuadi (Ikatan Dai Indonesia, 2025)
This mini-research examines the procurement of a Management Information System (SIM) at SMP Telkom Purwokerto, focusing on the role of administration in the procurement process, the challenges faced, and the strategies implemented. The digitalization era has brought significant changes to education, where the use of information and communication technology (ICT) is crucial for improving administrative efficiency and the quality of learning. This research uses a qualitative approach with a case study method, involving field observations, in-depth interviews, and document studies to collect data. The research findings show that the implementation of SIM at SMP Telkom Purwokerto can improve data management and administrative processes, thereby accelerating attendance recording and student grade management. However, there are challenges in SIM procurement, such as limited budgets and human resource readiness. Administration plays a vital role in identifying system needs, ensuring that vendors meet qualifications, and providing training to users. The conclusion of this research emphasizes that the success of SIM procurement heavily relies on the administration's ability to manage the process effectively. With ongoing training and technical support, the challenges faced can be overcome, allowing SIM to function optimally and support better decision-making. This research is expected to serve as a model for other schools in implementing similar systems.